Out of Africa: A New Afrotheria Lineage Rises From Extinct South American Mammals - Avilla, Leonardo S.; Mothé, Dimila (Frontiers in Ecology and Evolution, 2021)
The South American Native Ungulates (SANUs) are usually overlooked in Eutherian phylogenetic studies. In the rare studies where they were included, the diversity of SANUs was underrated, keeping their evolutionary history poorly known. Some authors recognized the SANUs as a monophyletic lineage and formally named it Meridiungulata. Here, we recognized and defined a new Supraordinal lineage of Eutheria, the Sudamericungulata, after performing morphological phylogenetic analyses including all lineages of SANUs and Eutheria. The SANUs resulted as non-monophyletic, thus Meridiungulata is not a natural group; Litopterna and “Didolodontidae” are Panamericungulata and closer to Laurasiatheria than to other “Meridiungulata” (Astrapotheria, Notoungulata, Pyrotheria, and Xenungulata). The other “Meridiungulata” is grouped in the Sudamericungulata, as a new monophyletic lineage of Afrotheria Paenungulata and shared a common ancestor with Hyracoidea. The divergence between the African and South American lineages is estimated to Early Paleocene, and their interrelationships support the Atlantogea biogeographic model. Shortly afterward, the Sudamericungulata explosively diversified in its four lineages. Confronting the Sudamericungulata evolutionary patterns and the Cenozoic natural events (such as tectonics and climatic and environmental changes, among others) helps to unveil a new chapter in the evolution of Gondwanan Eutheria, as well as the natural history of South America during the Cenozoic.